Joint Retirement of Couples: Evidence from a Natural Experiment - Hans Bloemen; Stefan Hochgürtel; Jochem Zweerink (Institute for the Study of Labor (IZA), 2015)
We estimate and explain the impact of early retirement of husbands on their wives probability to retire within one year, using administrative micro panel data that cover the whole Dutch population. We employ an instrumental variable approach in which the retirement choice of husbands is instrumented with eligibility rules for generous early retirement benefits that were temporarily and unexpectedly available to them. We find that early retirement opportunities of husbands increased the wives' probability to retire by 24.6 percentage points. This is a strong, and robust effect. Partly, wives respond to husbands' choices at ages when they are themselves likely eligible for early retirement programs.
Keywords: C26; J26; J12; J14; 330; instruments; retirement; couples